Pengembangan Kreativitas Kuliner Sebagai Elemen Daya Tarik Wisata Kota Depok - Auliya, Anisatul; Mona, Nailul (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
This research about culinary creativity development was conducted in Depok City, West Java. Depok is a metropolitan city located near Jakarta, capital city of Indonesia. Depok has various local culinary that not known well yet. Whereas previous study shows that culinary is one of emerging tourism attractions. This research aim to describe dan propose strategy to develop culinary creativity in Depok City, and can attract tourist to visit and taste local culinary in Depok. Using interview and observation, research conducted on August 2019- January 2020. It was found that Depok City has potential in culinary and need to be improved using the mapping method of the culinary ecosystem. Depok has been applying creativity in creating attractive culinary experience, but chef competencies is need to be improved. This creativity must be completed with good promotion and publication, culinary events that held routinely and in a large scale,archiving and documentation, and prioritize traditional Indonesian cuisines. Keywords: Culinary; Tourism Attractions; Culinary Ecosystem